Measuring place identity in public open spaces - Polat, Sibel; DOSTOĞLU, NESLİHAN (Proceedings of The Institution of Civil Engineers-Urban Design and Planning, 2017)
There is a growing body of evidence that indicates that for creating civic consciousness and sustaining urban identity and memory people need civic interaction and social reconciliation, which are promoted by public open spaces. However, in an era of globalisation, public open spaces are mostly discussed in relation to privatisation, disappearance, obsolescence and loss of place identity, leading to urban decay problems in many city centres. The aim of this study is to propose a research method for monitoring changes in place identity in public open spaces to set the right objectives and policies in the design process of these spaces for keeping them alive and for sustaining public life. In this context, a case study was conducted in Bursa's Republic Square in Turkey, using different interpretive historical, quantitative and qualitative strategies. The main findings of the case study are that there has been a gradual decline in sense of place in recent years, although the architectural and artistic elements of the area and the name of the place are still effective in defining the identity of the area.
Keywords: design methods & aids; history; town & city planning